2000
DOI: 10.1203/00006450-200008000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System Dysfunction in Adolescents with Postural Orthostatic Tachycardia Syndrome and Chronic Fatigue Syndrome Is Characterized by Attenuated Vagal Baroreflex and Potentiated Sympathetic Vasomotion

Abstract: The objective was to determine the nature of autonomic and vasomotor changes in adolescent patients with orthostatic tachycardia associated with the chronic fatigue syndrome (CFS) and the postural orthostatic tachycardia syndrome (POTS). Continuous electrocardiography and arterial tonometry was used to investigate the heart rate and blood pressure responses before and 3-5 min after head-up tilt in 22 adolescents with POTS and 14 adolescents with CFS, compared with control subjects comprising 10 healthy adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
146
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(169 citation statements)
references
References 31 publications
(46 reference statements)
20
146
1
2
Order By: Relevance
“…13 In their assessment of both sympathetic baroreflex sensitivity and cardiovagal baroreflex sensitivity, the function of the autonomic nervous system was intact in the patients, 13 although other researchers have postulated autonomic nervous dysfunction with exaggerated sympathetic nervous activation over compensatory levels while standing as a major mechanism behind the symptoms. 4,5,20,24,27 Elucidation of the pathophysiology of CFS and OI may lead to better therapeutic strategies. Recently, xenon-computed tomography blood-flow studies demonstrated that CFS patients have global cerebral hypoperfusion with reduced absolute cortical blood flow in broad areas, especially in bilateral middle cerebral artery territories, compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…13 In their assessment of both sympathetic baroreflex sensitivity and cardiovagal baroreflex sensitivity, the function of the autonomic nervous system was intact in the patients, 13 although other researchers have postulated autonomic nervous dysfunction with exaggerated sympathetic nervous activation over compensatory levels while standing as a major mechanism behind the symptoms. 4,5,20,24,27 Elucidation of the pathophysiology of CFS and OI may lead to better therapeutic strategies. Recently, xenon-computed tomography blood-flow studies demonstrated that CFS patients have global cerebral hypoperfusion with reduced absolute cortical blood flow in broad areas, especially in bilateral middle cerebral artery territories, compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological mechanism of POTS is autonomic dysfunction, including vagal withdrawal with intact vasoactive barorefl exes and sympathoexcitation, which may contribute to vasomotor instability and orthostatic intolerance in these patients. 62) With regard to vascular function, Liao, et al demonstrated that abnormally augmented, fl ow-mediated dilation and abnormal function of the vascular endothelium may play important roles in POTS in children. 63) A study reporting that NOS3 alleles, which encode the predominant isoform of NOS in the vasculature, represent genetic factors associated with POTS also supports the contribution of the endothelium to the pathology of POTS.…”
Section: Mental Stressmentioning
confidence: 99%
“…11 After a minimum 15-minute waiting period, at least 500 beats were acquired during baseline supine conditions and during incremental tilts. I used custom software to collect RR intervals and systolic, diastolic, and mean BPs as sequences of discrete point events for each heart beat.…”
Section: Heart Rate and Bp Variabilitymentioning
confidence: 99%